2019
DOI: 10.1038/s41467-019-12331-1
|View full text |Cite
|
Sign up to set email alerts
|

Purified F-ATP synthase forms a Ca2+-dependent high-conductance channel matching the mitochondrial permeability transition pore

Abstract: The molecular identity of the mitochondrial megachannel (MMC)/permeability transition pore (PTP), a key effector of cell death, remains controversial. By combining highly purified, fully active bovine F-ATP synthase with preformed liposomes we show that Ca2+ dissipates the H+ gradient generated by ATP hydrolysis. After incorporation of the same preparation into planar lipid bilayers Ca2+ elicits currents matching those of the MMC/PTP. Currents were fully reversible, were stabilized by benzodiazepine 423, a lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
185
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(188 citation statements)
references
References 68 publications
3
185
0
Order By: Relevance
“…A turning point in the field was the revelation that the F1F0 ATP synthase could function as a component of the mPTP pore in one of two ways, by passing solutes either through the border between two ATP synthase monomers or through the c-subunit ring that spans the inner mitochondrial membrane [127,128], but this remains controversial [129]. In two independent studies, highly purified ATP synthase complexes were recently confirmed to possess channel activity consistent with the biophysical characteristics of the mPTP, strongly supporting the identification of the ATP synthase as the sole component of the mPTP pore [130,131]. Further, monomeric complexes were sufficient to mediate mPTP-like channel activity [131], thus distinguishing the channel functions of ATP synthase monomers from the role of ATP synthase dimers in mitochondrial cristae formation [132].…”
Section: Crosstalk Between Apoptosis and Mptpmediated Necrosismentioning
confidence: 89%
“…A turning point in the field was the revelation that the F1F0 ATP synthase could function as a component of the mPTP pore in one of two ways, by passing solutes either through the border between two ATP synthase monomers or through the c-subunit ring that spans the inner mitochondrial membrane [127,128], but this remains controversial [129]. In two independent studies, highly purified ATP synthase complexes were recently confirmed to possess channel activity consistent with the biophysical characteristics of the mPTP, strongly supporting the identification of the ATP synthase as the sole component of the mPTP pore [130,131]. Further, monomeric complexes were sufficient to mediate mPTP-like channel activity [131], thus distinguishing the channel functions of ATP synthase monomers from the role of ATP synthase dimers in mitochondrial cristae formation [132].…”
Section: Crosstalk Between Apoptosis and Mptpmediated Necrosismentioning
confidence: 89%
“…A self-standing field concerns with the mitochondrial permeability transition pore (mPTP), largely dependent on calcium homeostasis. Recently, mPTP was suggested to act as a non-physiological specific conformation of the ATP synthase and its oligomers [53]. However, this topic is beyond the scope of this review.…”
Section: The Interplay Between Ros Mitochondrial Anion Channels Andmentioning
confidence: 94%
“…Opening of this pore leads to mitochondrial dysfunction and cell death by either apoptosis or necrosis (53). Recent work on the components of the mPTP has implicated the c ring of the ATP synthase (56,57), a channel inside ATP synthase dimers (55,58), or the purified ATP synthase itself (59), as forming the pore. Interestingly, vestigial ATP synthases devoid of c subunits maintain mPTP formation features, suggesting that the c ring per se is not the channel (60).…”
Section: Specific Interaction Between Hsmcu and Hsatpc In Vitro And Imentioning
confidence: 99%